How to be a better.... interviewer - Dale, Margaret (Kogan Page The Industrial Society, 1996)
This text is designed to give practical advice to those conducting interviews. Subjects covered include: utilizing work samples within the interview; getting revealing answers to the most pertinent questions; deciding on interview technique; and putting candidates at ease.